Pendidikan Multikultural dalam Pluralisme Nasional - Faisal, Akhmad; Ruswandi, Uus; Erihadiana, Mohamad (Eduprof : Islamic Education Journal, 2023)
Multiculturalism and pluralism are evident characters within the instruction framework in Indonesia, particularly devout instruction. Through this concept, a sense of solidarity within the domain of ukhuwah basyariyah in advancing and making strides the quality of education will be built up; in this manner an instruction framework that produces religion as ethical values and not as a formal institution is shaped. The point of this inquire about is to discover out pluralism and multiculturalism considers. The methodology utilized is graphic expressive with attitude composing. The comes about of the inquire about appear that it could be a joint errand to create demeanors, acknowledge contrasts, and regard devout pluralism, coupled with reliance on and commitment to each religion, through learning rules and internalizing devout values. in teacher educating by upgrading learning materials and their meaning for understudies, acing learning techniques, and perusing materials that can back the improvement of all understudies.